Research and Strategic Analysis of New Generation Telecom IT System Disaster Recovery System - Dezhi Gong; Yirong Shi (Dianxin kexue)
The latest disaster recovery technology was stated and classification principles into critical business systems was elaborated. Also, the architecture of a new generation of disaster recovery technology program was analyzed by taking one branch of China Telecom as an example.